Autonomous and in trans functions for the two halves of Srv2/CAP in promoting actin turnover. Issue 6 (25th April 2014) - Chaudhry, Faisal; Jansen, Silvia; Little, Kristin; Suarez, Cristian; Boujemaa‐Paterski, Rajaa; Blanchoin, Laurent; Goode, Bruce L.
<x xml:space="preserve">Abstract</x> Recent evidence has suggested that Srv2/CAP (cyclase‐associated protein) has two distinct functional roles in regulating actin turnover, with its N‐terminus enhancing cofilin‐mediated severing of actin filaments and its C‐terminus catalyzing actin monomer recycling. However, it has remained unclear to what degree these two activities are coordinated by being linked in one molecule, or whether they can function autonomously. To address this, we physically divided the protein into two separate halves, N‐Srv2 and C‐Srv2, and asked whether they are able to function in trans both in living cells and in reconstituted assays for F‐actin turnover and actin‐based motility. Remarkably, in F‐actin turnover assays the stimulatory effects of N‐Srv2 and C‐Srv2 functioning in trans were quantitatively similar to those of intact full‐length Srv2. Further, in bead motility assays and in vivo, the fragments again functioned in trans, although not with the full effectiveness of intact Srv2. From these data, we conclude that the functions of the two halves of Srv2/CAP are largely autonomous, although their linkage improves coordination of the two functions in specific settings, possibly explaining why the linkage is conserved across distant plant, animal, and fungal species. © 2014 Wiley Periodicals, Inc.